Resilience of Civiliarchic Democracy in the Face of Challenges and Gaps in European Integration: The Political Dimension of the Index of Civiliarchy - Ashot Aleksanyan; Arusyak Aleksanyan (Journal of Political Science: Bulletin of Yerevan University)
The Eastern Partnership (EaP) countries face significant challenges in achieving democratic consolidation amid geopolitical tensions, authoritarian tendencies and regional conflicts. This paper examines the resilience of civiliarchic democracy as a framework to understand and address these challenges. The study employs a mixed methods approach including comparative analysis and the Civiliarchy Index to explore the interplay between European integration, democratic resilience and anti-civiliarchic forces.  To identify the main principles of EU foreign policy in the EaP countries and its normative component, a qualitative targeted content analysis of official EU documentation was used. Additionally, the method of discourse analysis was used to consider the narrative regarding the participation and lobbying from the EU and European institutions and values within the EaP countries, as well as prepare for the negotiations with EU and EU member states for the interests of EaP countries. Europeanization and democratization determine both the political and social prospects for sustainable development of the EaP countries, as well as the hybrid challenges of strategic security and the dichotomy of inter-integration conflicts.  The paper analyzes the gaps in European political integration in the EaP countries for the period from 2013 to 2023. The authors rely on studies on Europeanization and European political integration in the tradition of neo-institutionalism, as well as on the resilience of the EaP countries. The findings of the paper imply that the civiliarchic democracy the EaP countries face is thwarted by internal instability, external pressures and shortcomings in EU policies. But EU’s strategic and engagement can in some extent tackle authoritarian trends and improve democratic institutions. Theoretical and practical insight into the concept of civiliarchic democracy and its resiliency in light of the democratization literature is the main contribution of the study. Policy and scholarly implications of the findings in support of improving democratic institutions and further inclusive European integration in the EaP region are suggested.